Implementation of Situational Crisis Communication Theory on the Case of Covid-19 by the Government of West Jawa through @pikobar_jabar - Rizkiya Ayu Maulida (BBPSDMP KOMINFO MAKASSAR, 2021)
This study aims to explore the crisis communication strategy of West Java Provincial Government on handling Covid-19 through the @pikobar_jabar Instagram account. According to SCCT, there are two functions of crisis communication, namely to ensure public safety and manage the reputation of the organization. This research was conducted using a qualitative content analysis method, where the researcher examined the content of Instagram @pikobar_jabar in the period of March-April 2020. The results showed that The West Java Regional Government used the Instagram account @pikobar_jabar to disseminate instructions on handling Covid-19 and at the same time publish their performance in overcoming the crisis. However, there are more posts contained instruction than performance publication. Hence, the West Java Regional Government prioritize public’s safety, rather than managing the image of their institution. In addition, researchers also found that in providing instructive messages, @pikobar_jabar used a persuasive strategy, which combines logical, emotional, and emotional aspects to create behavior changes.